The Battle of the Atlantic, the “Air Gap,” and the Delay in Allocating Liberators to the Royal Canadian Air Force - Bell, Christopher M. (The Northern Mariner / Le marin du nord, 2025)
The gravest crisis of the Battle of the Atlantic came in the latter part of 1942 and early 1943 when German submarine forces concentrated in the central ocean, the “air gap” beyond the reach of shore based Allied maritime air forces. More capable aircraft were available, but not assigned to the maritime role until the spring of 1943. This article proposes a new methodology for understanding the reasons for the delay by examining the complex interactions among the navies, air forces, and politicians of the three Allied powers primarily responsible for trade defence in the Atlantic Ocean – Great Britain, the United States, and Canada – and exploring the special difficulties faced by the Royal Canadian Air Force.